Transformasi digital tata usaha sekolah: strategi pengelolaan administrasi berbasis teknologi informasi - Salaf, Mila Rosita Manhaj; Elviera, Chyntiya Dewiy (Jurnal Madako Education, 2025)
This journal discusses the development of computer-based school administration by utilising advances in information technology to modernise educational governance. School administration plays a crucial role as the spearhead of services within an academic foundation, both internally and externally. Although administration is an essential unit for supporting institutional activities, the performance of administrative staff is still less than optimal in providing services effectively and efficiently. This condition indicates the need for an information technology-based administration system to improve productivity, data accuracy, and the quality of educational services. The purpose of this study is to review the implementation and effectiveness of an information technology-based administration system in improving school administrative performance. The research method used is descriptive qualitative through direct observation of real conditions in the field. The results show that the application of information technology in school administration can accelerate the service process, improve the accuracy of data management, and support transparency and accountability in educational management.